Efektivitas Penggunaan Metode Mind Mapping untuk Meningkatkan Kreativitas Siswa dalam Pembelajaran - Meilina, Duwi; Hanafiah, Nur Arifah; Fatmawan, Aditya Ridho; Hamzah, Muh. Zuhdy; Ulimaz, Almira; Priyantoro, Dian Eka (CV. Creative Tugu Pena, 2024)
This study aims to explore the effectiveness of mind mapping method in enhancing students' creativity. Involving research subjects in the form of junior high school students in Way Kanan, Lampung, a qualitative approach was used to collect data through classroom observation, interviews, and mind map document analysis. The results showed that the use of the mind mapping method positively contributed to students' creativity through the flexibility of idea representation, development of problem-solving ability, and construction of creative associations. The findings have practical relevance by suggesting integrating the mind mapping method in learning design at junior high school level to create a supportive environment for students' creativity development. While this study provides valuable insights, future research can go into more depth by exploring the factors that influence the effectiveness of the mind mapping method and using a quantitative approach for further validation. Keywords: Mind Mapping, Student's Creativity, School Learning